Effect of Thermal Manipulation During Embryogenesis on Pre and Post-Hatch Performance of Stored Hatching Eggs of Japanese Quails - Nasir Abdallah; Kadriye Kursun; Mikail Baylan (Turkish Journal of Agriculture: Food Science and Technology)
This research investigated the influence of high incubation temperature on hatching, and post-hatch characteristics of stored hatching eggs of Japanese quails. Hatching eggs of Japanese quails were stored for 7 days and incubated under two temperature conditions. The T1 group (control, 75 eggs) was subjected to a standard incubation temperature (37.5°C) while the T2 group (75 eggs) was exposed to a thermal manipulation protocol (of 38.5°C for 5 hours daily between embryonic days 5-15. The egg weight classification, chick weight, chick length, wing length, weekly body traits, body weight, total feed intake, and stress responses, weight of internal organs, whole carcass, breast, neck, wing, thigh, and neck did not significantly differ (P<0.05) between the incubation treatments. Hatchability was higher and early embryonic mortality was lower in T2 than in T1. Late embryonic mortality was lower in T1. Significantly (P≤ 0.05) higher pectoral muscle width at hatch and carcass yield/dressing percentage were observed in quails exposed to thermal manipulation protocol during embryogenesis. It was concluded that exposure of stored eggs to thermal manipulation protocol (of 38.5°C for 5 hours between embryonic days, ED 5-15, T2) during embryogenesis could enhance embryonic and growth traits, as well as carcass traits without any negative effect on stress indicators.